2016
DOI: 10.4025/actascianimsci.v38i4.32147
|View full text |Cite
|
Sign up to set email alerts
|

<b>Morphogenesis and structure of Tifton 85 cultivated in subtropical climate and fertilized with nitrogen

Abstract: The experiment evaluated the morphogenesis and structure of Tifton 85 (Cynodon spp.) cultivated in subtropical climate and fertilized with nitrogen (N). The experiment was a completely randomized design with four levels of N (Zero; 75; 150 or 225 kg ha-1) in nine replicates per area. The experimental animals were Suffolk female lambs. The grazing method was continuous to maintain the sward height at 15 cm ± 10%. The stem expansion increased by 0.000027 cm degree-days-1 to each kg N applied (linear model). Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…The average canopy height of the first crop was 20.5 cm, whereas that of the second crop was 46.6 cm, a difference that could be attributed to the higher precipitation after the first harvest (Figure 1) and also the greater responsiveness of the second crop to N fertilization (Oliveira et al, 2010). Our results were similar to those reported by Tiecher et al (2016), which found that canopy height increased in relation to the N rate and rainfall. No significant differences were identified in the number of tillers per square meter among the N rates ( Figure 2) and no interaction was observed between the production periods or among the N rates.…”
Section: Resultssupporting
confidence: 80%
“…The average canopy height of the first crop was 20.5 cm, whereas that of the second crop was 46.6 cm, a difference that could be attributed to the higher precipitation after the first harvest (Figure 1) and also the greater responsiveness of the second crop to N fertilization (Oliveira et al, 2010). Our results were similar to those reported by Tiecher et al (2016), which found that canopy height increased in relation to the N rate and rainfall. No significant differences were identified in the number of tillers per square meter among the N rates ( Figure 2) and no interaction was observed between the production periods or among the N rates.…”
Section: Resultssupporting
confidence: 80%
“…The absence of N levels effect on leaf and stem expansion rates is not the usually reported answer when studies involve these two factors. These responses showed that, generally, as the nitrogen fertilization increase, a higher expansion rate of these components is observed (HUNDERTMARCK et al, 2017;TIECHER et al, 2017). Observations showed; however, a similar rate of leaves and stems expansion in the absence or presence of N fertilization.…”
Section: Discussionmentioning
confidence: 82%
“…The grazing method was continuous with a variable SR. Two testers per paddock were used. The adjustments in forage mass (FM) were based on the pasture height, maintained at 15-20 cm (Tiecher et al, 2016). The measurements were performed every 15 days with a ruler at 20 random points within each paddock.…”
Section: Pasture Management and Irrigationmentioning
confidence: 99%